Pediatric Posttonsillectomy Hemorrhage: Demographic and Geographic Variation in Health Care Costs in the United States. (August 2016) - Harounian, Jonathan A.; Schaefer, Eric; Schubart, Jane; Carr, Michele M.
Objective: To examine variations in management of pediatric posttonsillectomy hemorrhage and associated costs from a national third-party payer perspective. Study Design: The MarketScan database was analyzed for claims made for 30 days following tonsillectomy/adenotonsillectomy between 2008 and 2012 for privately insured children aged 1 to 17 years. Costs for management of postoperative hemorrhage by age, sex, and region were calculated in addition to total costs incurred for 30 days postoperatively. Setting: MarketScan database. Subjects and Methods: Database study. Results: A total of 305, 860 children were included. Overall, 0.3% had a postoperative bleed that required treatment but not surgical intervention or admission for hospitalization; 0.2% had one that required hospitalization; and 0.8% had one that required surgical intervention. The mean 30-day costs were $7660 for postoperative bleed that required surgery or hospitalization, $4580 for outpatient treatment, and $370 for no postoperative bleed. Children between 11 and 17 years old were most likely to have interventions for postoperative bleeding but had the lowest mean costs for them ($7320 for hospital based, $3860 for outpatient). There were regional differences in costs for in-patient management of bleeds, with highest costs in the West, with a mean of $8850, versus the South, with a mean of $7160. Conclusions: There are geographic and demographic variations in managing pediatric posttonsillectomy hemorrhage and in the costs associated with management on a national level.